Analisa dan Perancangan Ulang Antarmuka Aplikasi Teman Diabetes Terhadap Lansia - Anthony Aprian; Danny Sebastian; Restyandito Restyandito (AITI, 2022)
This study focuses on the redesign of Teman Diabetes application interface for the elderly aged 60 – 71 years. The goal is to give the elderly the confidence in using technology so as to improve their quality of life. Teman Diabetes application is the object of research that is being tested, because there are several interface deficiencies that can affect the elderly understanding. The method used is Usability Test method with ISO/IEC 9126-4 standardization and User Centered Design. Through this method, several changes in the appearance of the Teman Diabetes application were obtained based on the needs of the elderly, for example such as text size, buttons, textfields, etc. Then based on these changes found the value of the analysis results, namely, effectiveness 89 percent, efficiency 85 percent, and satisfaction 73 percent. Based on these changes and values, it can be said that the redesigned appearance of the Teman Diabetes application for the elderly has been accepted by users.